Multidisciplinary design methodology for mechatronic systems based on interface model - Zheng, Chen; Hehenberger, Peter; Le Duigou, Julien; Bricogne, Matthieu; Eynard, Benoît (Research in engineering design, 2017)
Mechatronic system is considered as the resulting integration of electrical/electronic system, mechanical parts and information processing. Therefore, to enable a systematic design process of mechatronic systems with a high-level integration, the so-called multidisciplinary integrated design is required. However, neither academia nor industry has yet provided an effective solution, which can fully support the whole design process to achieve such multidisciplinary integrated design. In order to organise the design activities from different disciplines and to aid the designers to achieve the multidisciplinary integrated design, the authors propose a design methodology based on a multidisciplinary interface model. In line with the systems engineering practices, an extended V-model is used as the macro-level process in the proposed design methodology. It starts with identification of requirements on the entire system and ends with a user-validated system. The hierarchical design model is adopted as the micro-level process. It supports the specific design phases where individual designers can structure design sub-tasks and proceed and react in unforeseen situations. To ensure the consistency and traceability between the two levels, the multidisciplinary interface model is proposed. This design methodology is demonstrated by studying the design process of a quadrotor.